Efficacy, safety and pharmacokinetics of candesartan cilexetil in hypertensive children from 1 to less than 6 years of age - Schaefer, Franz; Walle, Johan van de; Zurowska, Aleksandra; Gimpel, Charlotte; Hoeck, Koen van; Drozdz, Dorota; Montini, Giovanni; Bagdasorova, Ingretta V.; Sorof, Jonathan; Sugg, Jennifer; Teng, Renli; Hainer, James W. (Journal of hypertension, 2010)
Background - Few antihypertensive drugs are available in appropriate formulations for infants. - Method - We investigated candesartan cilexetil liquid suspension in a 4-week, randomized double-blind dose-ranging study followed by a 1-year open-label treatment phase (NCT00244621). The drug was administered at 0.05, 0.2 or 0.4 mg/kg per day in 93 hypertensive children aged 1-5 years, of whom 74 had underlying renal disorders. - Results - A single-dose pharmacokinetic profile was obtained in 10 patients. At 4 weeks, SBP declined dose dependently by 6, 9 and 12 mmHg in the three dose groups (P = 0.01), and DBP by 5, 8 and 11 mmHg (P = 0.03). During the 1-year follow-up, responder rates (both SBP and DBP < 95th percentile) ranged from 48.2 to 54.1%. Candesartan lowered the blood pressure regardless of age, sex, BMI or cause of hypertension. The pharmacokinetic profile was independent of age, sex and weight, and was similar to that in older children and adults. In participants with proteinuric renal disease (urinary albumin/creatinine ratio >30 mg/g), a 57% median decline in albumin/creatinine ratio was observed at 4 weeks, which was dose related (P = 0.007) and persisted with long-term administration. There were no notable electrocardiographic or laboratory abnormalities. A mild decline in estimated glomerular filtration rate observed at 4 weeks was not progressive with long-term dosing. Candesartan was generally well tolerated; two patients withdrew for adverse events (fatigue and worsening glomerulopathy). One patient died, probably from acute-on-chronic renal failure. - Conclusion - Candesartan cilexetil dose-dependently decreases blood pressure and albuminuria in hypertensive infants and is generally well tolerated.
Gesehen am 09.08.2023